Collaboration and complexity: an experiment on the effect of multi-actor coupled design. (July 2016) - Grogan, Paul; Weck, Olivier
Abstract Design of complex systems requires collaborative teams to overcome limitations of individuals; however, teamwork contributes new sources of complexity related to information exchange among members. This paper formulates a human subjects experiment to quantify the relative contribution of technical and social sources of complexity to design effort using a surrogate task based on a parameter design problem. Ten groups of 3 subjects each perform 42 design tasks with variable problem size and coupling (technical complexity) and team size (social complexity) to measure completion time (design effort). Results of a two-level regression model replicate past work to show completion time grows geometrically with problem size for highly coupled tasks. New findings show the effect of team size is independent from problem size for both coupled and uncoupled tasks considered in this study. Collaboration contributes a large fraction of total effort, and it increases with team size: about 50–60 % of time and 70–80 % of cost for pairs and 60–80 % of time and 90 % of cost for triads. Conclusions identify a role for improved design methods and tools to anticipate and overcome the high cost of collaboration.